Pemanfaatan Media Digital Dalam Pelestarian Permainan Tradisional Masyarakat Bebekan Selatan Kota Sepanjang - Safrial Anggra W; Nicolas Ravanelly M; Rafil Naufal Y; Shella Shofiyannajah; Fadhilah Yunviani H; Dwi Prasetyo (Prapanca : Jurnal Abdimas, 2021)
Gadget are now like a part of people’s lives. With our gadgets, it is very easy in many aspects of ctivities. But instead od being lulled by the convenience and sophistication of today’s gadgets, we also need to limit it.Especially children who are underage, the use of gadgets should be limited and can be given or introduced to children’s traditional games, besides teaching culture, traditional game can also shape children;s character and social skills. In addition, digital media also has and influence to introduce and disseminate traditional games. The targets of this service activity are children and members of the Karang Taruna Bebekan Selatan RT 24, RW 07 hamlet, Taman sub-district, Sidoarjo district, Jawa Timur Province. Karang Taruna members have a passion for enriching knowledge about socisl media content (Photography, Videography, Graphic Design), seen in the application of the lesson that have been given. And the children are very enthusiastic when playing traditional games. With the service activities, it it hoped that Karang Taruna members will continue to enrich content as a form of utilizing digital media and can preserve traditional games and in the future be able to introduce them to the surrounding environment.